Modifying factors in sports-related concussion: dangerous style of play - Diamond, A. B.; Solomon, G. S. (The Physician and Sportsmedicine, 2014)
In its third iteration, the Concussion in Sport Group identified 10 modifying factors that were presumed clinically to influence the investigation and management of concussions in sports. "Dangerous style of play" was delineated as one of these factors, most likely based on clinical lore. These modifying factors were retained in a more recent Concussion in Sport Group statement. To date, there has been no concerted effort to support or refute the inclusion of this constellation of behaviors as a modifying factor in sports-related concussion. This article reviews and summarizes the limited evidence related to a dangerous style of play in sports-related concussion, offers a preliminary assessment of its relevance as a modifying factor, and provides additional information on other aspects of player, coach, and governing body behavior and their potential effect(s) on reducing concussive injuries.